Proposing BCG Vaccination for Mycobacterium avium ss. paratuberculosis (MAP) Associated Autoimmune Diseases - Coad Thomas Dow (Microorganisms, 2020)
Bacille Calmette−Guerin (BCG) vaccination is widely practiced around the world to protect against the mycobacterial infection tuberculosis. BCG is also effective against the pathogenic mycobacteria that cause leprosy and Buruli’s ulcer. BCG is part of the standard of care for bladder cancer where, when given as an intravesicular irrigant, BCG acts as an immunomodulating agent and lessens the risk of recurrence. Mycobacterium avium ss. paratuberculosis (MAP) causes a fatal enteritis of ruminant animals and is the putative cause of Crohn’s disease of humans. MAP has been associated with an increasingly long list of inflammatory/autoimmune diseases: Crohn's, sarcoidosis, Blau syndrome, Hashimoto’s thyroiditis, autoimmune diabetes (T1D), multiple sclerosis (MS), rheumatoid arthritis, lupus and Parkinson’s disease. Epidemiologic evidence points to BCG providing a “heterologous” protective effect on assorted autoimmune diseases; studies using BCG vaccination for T1D and MS have shown benefit in these diseases. This article proposes that the positive response to BCG in T1D and MS is due to a mitigating action of BCG upon MAP. Other autoimmune diseases, having a concomitant genetic risk for mycobacterial infection as well as cross-reacting antibodies against mycobacterial heat shock protein 65 (HSP65), could reasonably be considered to respond to BCG vaccination. The rare autoimmune disease, relapsing polychondritis, is one such disease and is offered as an example. Recent studies suggesting a protective role for BCG in Alzheimer’s disease are also explored. BCG-induced energy shift from oxidative phosphorylation to aerobic glycolysis provides the immunomodulating boost to the immune response and also mitigates mycobacterial infection—this cellular mechanism unifies the impact of BCG on the disparate diseases of this article.